2004
DOI: 10.1002/bjs.4468
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic laparoscopy and diverting sigmoid loop colostomy in the management of civilian extraperitoneal rectal gunshot injuries

Abstract: Low-velocity gunshot injuries isolated to the extraperitoneal rectum can be managed safely by laparoscopic exclusion of intraperitoneal missile penetration and diverting sigmoid loop colostomy, without laparotomy, distal rectal washout or presacral drainage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…However, some extraperitoneal injuries like our case are difficult to repair because their anatomical location is too low for a transabdominal approach and too high for a transanal approach. These cases can be managed safely with a proximal diverting colostomy alone, without repair of the perforation [3][4][5]. Therefore, we performed diverting sigmoid loop colostomy only without looking for the perforation site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some extraperitoneal injuries like our case are difficult to repair because their anatomical location is too low for a transabdominal approach and too high for a transanal approach. These cases can be managed safely with a proximal diverting colostomy alone, without repair of the perforation [3][4][5]. Therefore, we performed diverting sigmoid loop colostomy only without looking for the perforation site.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we performed diverting sigmoid loop colostomy only without looking for the perforation site. Previous evidence reported the usefulness of diagnostic laparoscopy and laparoscopic diverting loop sigmoid colostomy in low-velocity gunshot injuries with extraperitoneal rectal injuries [4,5]. However, in South Korea, in terms of the law, the occurrence of the gunshot injuries is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] In the treatment of extraperitoneal rectal injuries, a diverting colostomy has been accepted as the standard therapy by many authors. [7][8][9] It has been reported that extraperitoneal rectal injuries can be safely treated with fecal diversion alone, particularly in low-velocity trauma. [10,11] Bostick et al [7] reported that no septic complications were observed in any of the cases that underwent loop colostomies.…”
Section: Discussionmentioning
confidence: 99%
“…Mientras varios autores continuaban preconizando el drenaje presacro sistemático 7,34,37 otros creían que su uso debía ser selectivo según las características de las lesio-nes 20,35,38,39,40 . Otro tanto sucedió con el uso del lavado rectal distal, apoyado por algunos para ser empleado siempre 38,41 mientras que otros solo lo llevaban a cabo en casos seleccionados 7,20,34,35,40 . De este modo llegamos hasta la actualidad, en la cual existe falta de consenso con respecto al óptimo manejo quirúrgico del TRE 36 en el medio civil.…”
Section: Abcddv/581unclassified